The Chinese version of the immediate mood scaler (IMS): a study evaluating its validity, reliability, and responsiveness in patients with MDD in China - Xiongying Chen; Zizhao Feng; Nanxi Li; Le Xiao; Xu Chen; Xuequan Zhu (BMC Psychiatry)
Abstract Background It is important to timely capture the fluctuation of the symptoms related to major depressive disorder (MDD). However, most conventionally used assessment tools for MDD symptoms are not designed for real-time assessment. The Immediate Mood Scaler (IMS) is suitable for the real-time evaluation of the mood of patients with MDD. Methods The original IMS was translated into Chinese and back-translated. At baseline, data from 368 patients with MDD, including demographic information and scores on the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and IMS, were collected. In total, 185 participants completed the retest at Week 2 which included the PHQ-9, GAD-7, and IMS. Internal structural validity, construct validity, and internal consistency were evaluated with the confirmatory factor analysis (CFA), the Pearson correlation, and Cronbach’s α, respectively. Responsiveness was anchored by the change of the PHQ-9 total scores from baseline to Week 2 and predictability was tested using the multivariate linear mixed model for repeated measures (MMRM). Results Two factors with an eigenvalue greater than 1, corresponding to IMS-Depression and IMS-Anxiety subscales, were identified using CFA. The Cronbach’s α that evaluated internal consistency was 0.96, 0.95, and 0.92 for the scores of the IMS, IMS-Depression subscale, and IMS-Anxiety subscale at baseline, respectively. The depression and anxiety subscales at baseline showed high subscale-total correlations (r = 0.96 for the depression subscale; r = 0.89 for the anxiety subscale). The test-retest ICC (0.65, 95%CI: 0.53–0.73) of the IMS at baseline and Week 2 show high reliability. The total score of IMS had significant correlations with that of the PHQ-9 (r = 0.52, P < 0.001) and GAD-7(r = 0.43, P < 0.001), indicating good construct validity. In patients with MDD who showed changes in mood, the changes in total scores of the IMS from baseline to the retest were statistically significant with a mean difference of 13.3 (SD: 20.1), an ES of 0.66, and an SRM of 0.3, showing good responsiveness. Also, the baseline IMS-Depression subscale score could predict the change in the PHQ-9 score over the two weeks (t = 2.19, P = 0.029). Conclusions Study findings suggest that the Chinese version of the IMS is a valid and reliable tool for assessing mood symptoms in patients with MDD in China. Further validation studies of the Chinese version IMS in different regions and at various levels of medical institutions are needed to further confirm the current findings.